Strategy for preserving the ithuk-ithukan tradition as the cultural identity of the Osing tribe in Rejopuro Hamlet, Banyuwangi - Putri, Nabila Syakila; Harianto, Sugeng; Putri, Rizky Trisna (CV. Kurnia Grup, 2025)
This study examines strategies for preserving the Ithuk-ithukan tradition as part of the cultural identity of the Osing tribe in Rejopuro Hamlet. The research focuses on how this tradition is passed down and preserved amid modern social changes. The objectives of the study are to investigate preservation practices, the role of the younger generation, and technological adaptation efforts in maintaining cultural sustainability. The method used is qualitative research with a case study approach, involving interviews with traditional leaders, participatory observation, and documentation of ritual activities. The results show the active involvement of the younger generation in ritual processions, the making of Ithuk, and the use of social media as a means of education and cultural preservation. The involvement of traditional leaders as cultural mentors has proven vital in maintaining traditional values and the continuity of rituals. The conclusion of the study confirms that a combination of cultural, social, and technological approaches is an effective strategy for preserving the Ithuk-ithukan tradition. Recommendations include increasing government support, empowering the younger generation, and optimizing information technology for sustainable cultural prese rvation. This research makes an important contribution to the study of anthropology and cultural sociology in Indonesia and provides a basis for the development of cultural policies that are responsive to social dynamics.